HDAC1 is involved in the destabilization of the HSF2 protein under nonstress and stress conditions - Daupin, Kevin; Dubreuil, Véronique; Ahlskog, Johanna K.; Verrico, Annalisa; Sistonen, Lea; Mezger, Valérie; de Thonel, Aurélie (ELSEVIER SCIENCE INC, 2026)
Heat shock transcription factors 1 and 2 (HSF1 and HSF2) are the major regulators of the cellular response to stressors, notably to heat shock and to oxidative stress. HSF1 and HSF2 are also important contributors in devastating human pathologies like cancer, neurodegenerative disorders, and neurodevelopmental disorders. Under physiological conditions, nuclear HSF2 is detected in only a few cell types in human adult healthy tissues. In contrast, HSF2 protein levels are elevated at some embryonic stages, but greatly vary among cell types and fluctuate during the cell cycle in diverse cell lines. HSF2 is a short-lived protein whose rapid turnover is controlled by the components of the ubiquitin-proteasome degradation pathway, and the stabilization of HSF2 constitutes an important step that regulates its DNA-binding activity and mediates its roles in nonstress, physiological processes. The control of HSF2 abundancy is therefore critical for its regulatory roles in stress responses as well as under physiological conditions. In this regard, the fetal brain cortex is a singular context where HSF2 is strikingly abundant, exhibits constitutive DNA-binding activity and, by controlling a specific repertoire of target genes that play important roles at multiple steps of neurodevelopment. Recently, we showed that the lysine-acetyl-transferases CBP and EP300 stabilize the HSF2 protein under both unstressed and stressed conditions and that the integrity of the CBP/EP300-HSF2 pathway is important for neurodevelopment. Here, we identify the lysine-deacetylase histone-deacetylase 1 (HDAC1) as a novel HSF2-interacting protein partner and regulator, in an unbiased manner, and show that HSF2 and HDAC1 localize in the same cells in the developing mouse cortex and human cerebral organoids. We also demonstrate that HDAC1, through its catalytic activity, destabilizes the HSF2 protein, through HSF2 poly-ubiquitination and proteasomal degradation, under both normal and stress conditions.